THE EFFECT OF PKH FACILITATOR'S PERFORMANCE TOWARDS THE KPM'S SATISFACTION IN SUBDISTRICT OF SUWAWA TENGAH GORONTALO PROVINCE - Delviyanti Daud; Lisda L. Asi (JAMBURA: Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This research aims to know the effect of the Program Keluarga Harapan (PKH) Facilitator's performance in the Subdistrict of Suwawa Tengah Gorontalo Province. This research was conducted on the Keluarga Penerima Manfaat ((KPM) in the Subdistrict of Suwawa Tengah, Gorontalo Province by distributing questionnaires to respondents who have met the predetermined sample standards so that the data in this research are primary. The population in this study was 329 people and 77 samples were taken out of that population. Data collection was obtained from observations, questionnaires, and documentation. Data analysis used in this research was a simple regression. The analysis was conducted with SPSS 23. The result shows that there is a significant relationship between the variable of facilitator performance and the satisfaction of the Keluarga Penerima Manfaat (KPM) with the value of rhitung6.195, more than the value of rtable 1,992. The value of R square is 0.339 or 33.9%, the variability of Keluarga Penerima Manfaat (KPM) can be explained by the facilitator performance variable while the remaining 66.1% can be explained by other variables not examined in this study such as motivation and supporting facilities for Keluarga Penerima Manfaat (KPM) satisfaction.